SCSI: the southern connecticut stellar interferometer - Horch, Elliott P; Weiss, Samuel A; Rupert, Justin D; Dimaio, Alex J; Nusdeo, Daniel A; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo; Giudice, Andrea (SPIE, 2016)
The construction of a new prototype visible-light intensity interferometer for use in stellar astronomy is described. The instrument is located in New Haven, Connecticut, at Southern Connecticut State University, but key components of the system are also portable and have been taken to existing research-class telescopes to maximize sensitivity and baseline. The interferometer is currently a two-station instrument, but it is easily expandable to several stations for simultaneous measurement using multiple baselines. The design features single photon avalanche diode (SPAD) arrays, which increase the throughput and signal-To-noise ratio of the instrument. Predicted system performance and preliminary observations will be discussed. © 2016 SPIE.
Keywords: Avalanche diodes; Design features; Intensity Interferometry; Interferometers; Interferometry; Particle beams; Photon Counting; Photon counting; Photons; Signal to noise ratio; Simultaneous measurement; Single Photon Avalanche Diode Arrays; Single photon avalanche diode; Single-photon avalanche diode arrays; Stars; Stellar interferometers; Timing Correlation; Ultra-High-Resolution Astronomy; Ultrahigh resolution; Visible light; dept.phy